Qingxuan Jiangya Decoction Mitigates Renal Interstitial Fibrosis in Spontaneously Hypertensive Rats by Regulating Transforming Growth Factor-β1/Smad Signaling Pathway. (26th December 2017) - Liu, Wangyu; Lin, Shan; Cai, Qiaoyan; Zhang, Ling; Shen, Aling; Chen, Youqin; Chu, Jianfeng; Peng, Jun
Abstract : Qingxuan Jiangya Decoction (QXJYD) is a traditional Chinese medicine commonly used in the clinical treatment of hypertension. Earlier studies had shown that QXJYD could inhibit the elevation of blood pressure in spontaneously hypertensive rats (SHRs) and prevent remodeling of arterial vessels. This study examines the therapeutic efficacy of QXJYD against elevated blood pressure using the SHR model, as well as the mechanisms behind its antihypertensive activity and protection against renal fibrosis. The results showed that QXJYD significantly attenuated the increase in blood pressure in SHRs and mitigated the development of renal interstitial fibrosis. In addition, QXJYD also robustly decreased the excess accumulation of extracellular matrix and attenuated the elevated expression of MMPs. The antihypertensive effects and renal protection of QXJYD were determined to be strongly associated with inhibition of TGF- β 1/Smad signaling pathway.